Judicial impartiality: a brief analysis on a dimension of judicial conduct (Research, Society and Development, 2021)
The work aims to present a dogmatic notion about the principle of judicial impartiality, addressing it, at first, from the perspective of the constitutional civil process. Furthermore, through bibliographic review, we sought to explain the international correspondence of this principle as an orientation of judicial conduct, bringing to light, a brief contribution of transnational law, as well as an overview of the main guidelines provided by the Principles of Judicial Conduct of Bangalore. And, by conclusion, we recorded the considerations extracted from empirical study, from which the duty of impartiality is perceived as a dogmatic orientation of difficult practical implementation, due to the human character of the judge, making him unable to fully exemption of value. Thus, the ideal of acting eminently impartial, was revealed only as an artificial orientation of behavior, due to consisting of an impractical duty in its entirety, since there would be no possibility of requiring judges, human beings, the untying of personal perceptions, experiences, principles and particular values at the time of the construction of the judicial decision. For this reason, the idea of impartiality can also be presented as a belief, based on which society maintains a minimal relationship of trust in the organs and agents that make up the justice system.